1991
DOI: 10.1037/0033-2909.109.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Biological and genetic contributors to violence: Widom's untold tale.

Abstract: In her review of the literature on the intergenerational transmission of violent behaviors, Widom (1989a) addressed the social issues but omitted all references to the relevant biological and genetic literature. This addition to her review introduces studies of criminality, delinquency, and violence from a behavioral genetic standpoint. There is clear evidence for a genetic role in criminality and for a physiological basis for violent behavior. The inclusion of such genetic and biological evidence is necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
4

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(114 citation statements)
references
References 45 publications
0
110
0
4
Order By: Relevance
“…For example, because parents who have histories of antisocial behavior (which is moderately heritable) 14 are at elevated risk of abusing their children, maltreatment may be a marker for genetic risk that parents transmit to children rather than a causal risk factor for children's conduct problems. 15 Evocative (or reactive) rGE refers to the association between an individual's genetically influenced behavior and the reaction of those in the individual's environment to that behavior. For example, the association between marital conflict and depression may reflect the tensions that arise when engaging with a depressed spouse rather than a causal effect of marital conflict on risk for depression.…”
Section: Rge: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, because parents who have histories of antisocial behavior (which is moderately heritable) 14 are at elevated risk of abusing their children, maltreatment may be a marker for genetic risk that parents transmit to children rather than a causal risk factor for children's conduct problems. 15 Evocative (or reactive) rGE refers to the association between an individual's genetically influenced behavior and the reaction of those in the individual's environment to that behavior. For example, the association between marital conflict and depression may reflect the tensions that arise when engaging with a depressed spouse rather than a causal effect of marital conflict on risk for depression.…”
Section: Rge: Mechanismsmentioning
confidence: 99%
“…The research conducted by the COGA group on GABRA2 illustrates this concept. Edenberg et al 45 found that GABRA2 was not only strongly linked to alcohol dependence, but also to brain oscillations in the beta frequency range (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Beta rhythms reflect a balance between excitatory and inhibitory networks of nerve cells and this balance is thought to be regulated by the GABA A receptor.…”
Section: Genotype-environment Associations: Challenges In Identifyingmentioning
confidence: 99%
“…There have been reports of early sexual and physical abuse among psychopathic offenders (Farrington, 2006) but the effects Prevalence and Correlates of Psychopathic Traits in the Household Population 23 are small and inconsistent, and any observed associations are not necessarily causal in nature (DiLalla & Gottesman, 1991). No information on circumstances of admission to a psychiatric hospital was available to explain associations with the Lifestyle and Antisocial factors.…”
Section: Prevalence and Correlates Of Psychopathic Traits In The Housmentioning
confidence: 99%
“…20 The association between familial adversity and mental health outcomes might be explained by rGE of two different kinds. 21 First, aggressive parents may transmit to their children both an adverse rearing environment and a genetic susceptibility toward developing psychopathology (passive rGE). Second, a child with a particular genotype may behave in ways that elicit harsh treatment (evocative rGE).…”
Section: Introductionmentioning
confidence: 99%